1996
DOI: 10.1177/0305735696241007
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Expression in Music Performance: Between the Performer's Intention and the Listener's Experience

Abstract: Nine professional musicians were instructed to perform short melodies using various instruments - the violin, electric guitar, flute, and singing voice - so as to communicate specific emotional characters to listeners. The performances were first validated by having listeners rating the emotional expression and then analysed with regard to their physical characteristics, e.g. tempo, dynamics, timing, and spectrum. The main findings were that (a) the performer's expressive intention had a marked effect on all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
371
5
18

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(427 citation statements)
references
References 29 publications
33
371
5
18
Order By: Relevance
“…In fact, their contribution to musical emotions is taken for granted. For example, Gabrielson and Juslin (1996) have studied in some detail how musicians convey different emotions by slightly and characteristically deviating from what is written in the score. The role of the interpreter as opposed to the contribution of the musical structure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, their contribution to musical emotions is taken for granted. For example, Gabrielson and Juslin (1996) have studied in some detail how musicians convey different emotions by slightly and characteristically deviating from what is written in the score. The role of the interpreter as opposed to the contribution of the musical structure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Même les variations de dynamiques qui permettent de moduler l'intensité ou plus exactement la tension perçue, sont dépen-dantes du temps et de la structure des phrases [Krumhansl 1996, Fredrickson 1995, Fredrickson 2000, Gagnepain 2001]. Les variations de timbre joueraient aussi un rôle important dans l'expressivité d'une performance musicale, bien qu'elles restent relativement peu étudiées en raison de la complexité à définir correctement le timbre [Gabrielsson 1996, Barthet 2008. Les caractéristiques des instruments à oscillations auto-entretenues comme le violoncelle ou la clarinette se prêteraient particulièrement bien à l'étude des variations expressives de timbre, puisque celles-ci peuvent aussi changer au cours d'une note.…”
Section: Une Question De Variationsunclassified
“…Ce type de déviations présente beaucoup plus de variabilités que celles dues à la structure musicale, étant donné que l'intention expressive de chaque musicien est fonction de sa personnalité propre et de son humeur du moment, alors que les caractéristiques structurelles sont les mêmes pour tout le monde. Les études qui s'y rapportent utilisent généralement certains adjectifs émotionnels [Gabrielsson 1988, Gabrielsson 1996, Bresin 2000, Mion 2010] ou sensoriels [Canazza 1997c, Canazza 1997a, Canazza 1997b, De Poli 1998], pour modifier l'inspiration du musicien avant la performance. Dans [Gabrielsson 1996] par exemple, il est montré que chaque intention émotionnelle des musiciens (joie, tristesse, colère, peur, tendresse, solennité) provoque des variations spécifiques dans les paramètres acoustiques, qui sont reproductibles par instrumentiste.…”
Section: Les Variations Dues à L'intention éMotionnelleunclassified
See 1 more Smart Citation
“…The relationship between musical emotion and acoustic parameters has been studied by many researchers. They suggested that tempo was one of the most important parameters for musical emotion [9][10][11]. However, most of these studies used short musical materials which varied performing tempo, and the relation between musical emotion and tempo has not been clarified in a large number of various musical pieces.…”
Section: Introductionmentioning
confidence: 99%